MRI of perianal fistulas in Crohn’s disease - Reginelli, Alfonso (Acta Biomed, 2020)
Perianal fistulas represent one of the most critical complications of Crohn’s disease (CD). Management and treatment need a multidisciplinary approach with an accurate description of imaging findings. AIM. This study aspires to assess the significative role of Magnetic Resonance Imaging (MRI) in the study of perianal fistulas, secondary extensions, and abscess in patients with CD. Therefore it is essential to standardize an appropriate protocol of sequences that allow the correct evaluation of disease activity and complications. METHODS: We selected and reviewed ten recent studies among the most recent ones present in literature exclusively about pelvic MRI imaging and features in CD. We excluded studies that weren’t in the English language. CONCLUSIONS: MRI has a crucial role in the evaluation and detection of CD perianal fistulas because, thanks to its panoramic and multiplanar view, it gives excellent anatomic detail of the anal sphincters. Today MRI is the gold standard imaging technique for the evaluation of perianal fistulas, mainly because this technique shows higher concordance with surgical findings than does any other imaging evaluation. Surgical treatment is often required in the management of perianal fistula in patients with CD, which often have complex perineal findings. (www.actabiomedica.it)